Biomass Yield of Switchgrass Cultivars under High‐ versus Low‐Input Conditions. Issue 2 (23rd February 2017) - Casler, Michael D.; Sosa, Sergio; Hoffman, Lindsey; Mayton, Hilary; Ernst, Calvin; Adler, Paul R.; Boe, Arvid R.; Bonos, Stacy A.
Abstract : Switchgrass ( Panicum virgatum L.) is undergoing development as a biomass crop to support conversion of cellulosic biomass to energy. To avoid the competition of biomass with food or feed crops, most commercialization proposals suggest that switchgrass should be grown exclusively on marginal lands that are not fit for food or feed production. The objective of this study was to investigate the potential for cultivar × environment interactions that would affect the methods and approaches for breeding and evaluating switchgrass cultivars, including both upland and lowland types, for high‐input versus low‐input types of environments. Biomass yield was measured on 14 cultivars that were present in 28 replicated field experiments representing seven regions, ranging from 75 to 100° W and spanning USDA Hardiness Zones 4 through 7. Region was the most important environmental factor interacting with cultivars, supporting the idea that the north‐central and northeastern United States should have independent switchgrass breeding programs. Cultivars interacted with soil phosphorus concentration in New Jersey and with depth of the A and B horizons in New York and showed mild interactions with rate of nitrogen fertilizer at several locations. Cultivar rank correlation coefficients between the two rates of nitrogen fertilization (100 vs. 0 kg N ha −1 ) ranged from 0.23 to 0.88, suggesting a possible benefit to breeding and selection without applied nitrogen fertilizer.